Issues of biological and agricultural treatment of municipal sewage sludge - Magdalena Urbaniak; Anna Wyrwicka; Edyta Kiedrzyńska; Sylwia Staniak; Anna Gałązka; Wojciech Tołoczko; Grzegorz Siebielec (ACTA INNOVATIONS, 2014)
Increase of sewage sludge production in Poland requires undertaking specific methodsfortheir utilization anddisposal. The reason is that sewage sludge, in addition to being rich in organic matter, and biogenic compoundssuch as nitrogen and phosphorus, which are beneficial from an agricultural point of view, also contain heavymetals, toxic organic pollutants such as persistent organic pollutants and polycyclic aromatic hydrocarbons,inorganic compounds such as silicates and clay,and pathogenic bacteria and other microbial contaminants.This implies problemswithfurther use of such polluted sludge as fertilizer in agriculture. The aim of this paperis to analyze the possibilities and limitations of natural management of sewage sludge, taking into account theireffects on the restoration and conservation of organic matter in the soil andthe yielding of plants. In addition,the main methods of treatment of pollutedsludgebefore introducingitinto the environmentare considered.